Insights into chemical aging of urban aerosols over Delhi, India - Kartika Pandey; Sumit Kumar Mishra; Bhanu Pratap Singh; Mukesh Khare; Sudhir Kumar Sharma; Avinash Chandra Pandey; Mamta Devi; Ajit Ahlawat (Atmospheric Environment: X)
Atmospheric particles can undergo aging as they are transported over long distances and mix with particles from other sources. This can lead to the accumulation of pollutants and the formation of complex aerosol mixtures with diverse chemical and physical properties. To investigate the process of aging in ambient atmosphere, 24h sampling of PM2.5 aerosol particles on Quartz microfiber filter with a tin substrate was carried out from November 2020 to March 2021 at CSIR-National Physical Laboratory, New Delhi (28°38'10″ N and 77°10′17'' E), using fine particle sampler. Based on the observations of weather and meteorological parameters, a few episodic cases have been selected, and samples were analyzed at bulk and individual particle level. The objective of the present study is to investigate the aging characteristics of aerosols, enabling us to understand the mixing of aerosols (at both bulk and individual particle levels) and the variation in fresh and deformed (aged with other species) graphitic content in the episodic cases. The Raman Spectroscopy technique employed measures the intensity of graphitic (G band; around 1580 cm−1) and disordered graphitic (D band; around 1320 cm−1) content of aerosols. Individual particle microscopic observations reveal the occurrence of open chain fractals of black carbon in variable monomer sizes, sometimes agglomerated with metals like Cu, Cr, Ca etc., along with the presence of S- rich and organic aerosols while the Raman Spectrum (bulk sample analysis) highlights graphitic and disordered (when graphite interacts with other chemical species) graphitic intensities. Comparing the intensities of heavy haze and moderate haze with non-haze days (for comparison purpose, March 23, 2021 with the lowest PM2.5 concentration ∼ 62 μg/m3, has been considered as a non-haze day), it was observed that the intensities recorded on haze days were 45 to 200 times higher for the G band and 43 to 93 times higher for the D band; while for moderate haze days, the intensities were 4 to 61 times higher for the G band and 2 to 29 times higher for the D band. These findings suggest chemical processing of BC during haze days.